Pengaruh Metode Role Playing terhadap Hasil Belajar Peserta Didik Kelas IV SD Inpres 48 Kabupaten Sorong - Ella Bless, Maria; Alfian Fitriani, Anis; Sri Astutik, Heny (Journal of Comprehensive Science, 2025)
The purpose of this study is to see the influence of the role playing method on student learning outcomes. The research used is qualitative research with the type of experimental research with Pre-Exsperimental Design. The sample in this study is grade IV students of SD Inpres 48 Sorong Regency which totals 23 students. This study uses posttest and pretest test techniques. The data results obtained used the results of statistical descriptions of pretest and posttest. From the data analysis, the Shapiro wilk normality test was obtained, which was 0.231 for the pretest and 0.253 for the posttest. If the significant value > 0.05, the data is declared to be normally distributed. The results of the N-Gain test data showed that the percentage of the mean value of the N-Gain score was 0.539 and the value was in the range of 0.30<N-Gain<0.70, included in the medium value criteria. The results of the data of one t-test sample showed that the T value was 87,241 with df which was 22. From this explanation, the p-value is 0.001 < a(0.05), then HO is rejected and H1 is accepted. Thus, it can be concluded that there is an influence of the role playing method on student learning outcomes.